Clinic, diagnostics, treatment and results of acute lung accesses in HIV-infected patients - P. M. Ionov; А. V. Elikin; I. V. Deinega; G. A. Yakovlev (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to study the course and results of treatment of lung abscesses in HIV-infected patients.METHODS AND MATERIALS. We analyzed the case histories of 199 patients with lung abscesses who treated in the Department of thoracic surgery of St. Petersburg Pokrovskaya Municipal Hospital in the period from 2012 to 2018. The 1st group included 121 HIV-infected patients, and the 2nd group – 78 patients with HIV-negative status.RESULTS. Patients from the 1st group were younger than patients from the 2nd group (p <0.05). Lung abscesses without sequestration were detected in 105 (86.8 %) patients in the 1st I group and 65 (83.3 %) in the 2nd group. Lung abscesses with sequestration (gangrenous abscesses) was diagnosed in 16 (13.2 %) HIV-infected and 13 (16.7 %) uninfected patients. There were no differences between surgical methods of treatment and outcomes (p>0.05). The mortality rate in the 1st group was 9.1 %, and in the 2nd – 12.8 %.CONCLUSION. General surgical methods for treating lung abscess are equally effective in patients with HIV-negative status and HIV-positive status. Lung abscesses in HIV-positive and HIV-negative patients have a similar etiology, clinical symptomatology, courses and outcome.